The role of iodine in cognitive development through thyroid hormones: Impacts during pregnancy, childhood, and adolescence - Dila Lintang Lintang Harmanto Harmanto Putri; Suyatno Suyatno; Ahmad Syauqy; Lilis Wijayanti; Dwi Yuniar Intan Sari; Ariny Poespitasari; Ayu Afrilia (AcTion: Aceh Nutrition Journal, 2026)
Iodine deficiency has been reported to re-emerge in developed countries, such as the United States and Taiwan, with significant cognitive consequences, despite inconsistencies in the existing body of evidence. Meanwhile, Indonesia lacks up-to-date data on population iodine status. This literature review aimed to examine the role of iodine in cognitive development and the impact of iodine deficiency at different life stages. The review employed a literature-based approach by searching English-language articles published between 2016 and 2025 using the Scopus, Google Scholar, PubMed, and ScienceDirect databases and the PRISMA analytical framework. The included studies were original research and review articles involving pregnant women, children, and adolescents. The findings indicate that iodine deficiency is associated with impaired cognitive function, particularly when exposure occurs during pregnancy. Adequate iodine intake through food fortification programs, supplementation, and consumption of iodine-rich foods supports optimal cognitive development. Therefore, continuous monitoring and strengthening of iodine fortification interventions are required to support human capital development. In addition, enhanced iodine supplementation programs for pregnant women, improved education on iodized salt consumption, and ongoing monitoring and evaluation of fortification programs are needed to update and strengthen iodine status data in Indonesia.